2017
DOI: 10.1007/s10877-017-0089-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of blood pressure monitoring by applanation tonometry and invasively assessed blood pressure in cardiological patients

Abstract: The aim of this study was to evaluate the accuracy and precision of non-invasive continuous blood pressure measurement by applanation tonometry (AT) in awake or anaesthetised cardiological intensive care patients. Patients suffering from highly impaired left ventricular function atrial fibrillation or severe aortic valve stenosis were included into the study. Arterial blood pressure was recorded by applanation tonometry (T-Line 400, Tensys Medical, USA) and an arterial line in awake or anaesthetised patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Similar studies on cardiac patients with severe cardiac comorbidities revealed the correlation coefficients for MAP, SAP and DAP to be 0.23, 0.45 and 0.06, respectively; the bias 14.96, 4.51 and 19.12 mmHg; the percentage errors 56.8, 42.7 and 75.2% accordingly. 62 Automated AP measurement tools were found acceptable for MAP, partially acceptable for DAP, and unacceptable SAP estimations in cardiovascular postsurgical intensive care patients. 63 Statistical analysis of twelve validations (566 patients; five home, three ambulatory and three office devices) revealed the automatic AP monitors are accurate in measuring SAP but not DAP in patients with atrial fibrillation.…”
Section: Applanation Tonometrymentioning
confidence: 94%
See 1 more Smart Citation
“…Similar studies on cardiac patients with severe cardiac comorbidities revealed the correlation coefficients for MAP, SAP and DAP to be 0.23, 0.45 and 0.06, respectively; the bias 14.96, 4.51 and 19.12 mmHg; the percentage errors 56.8, 42.7 and 75.2% accordingly. 62 Automated AP measurement tools were found acceptable for MAP, partially acceptable for DAP, and unacceptable SAP estimations in cardiovascular postsurgical intensive care patients. 63 Statistical analysis of twelve validations (566 patients; five home, three ambulatory and three office devices) revealed the automatic AP monitors are accurate in measuring SAP but not DAP in patients with atrial fibrillation.…”
Section: Applanation Tonometrymentioning
confidence: 94%
“…57 Recent studies on simultaneous measurements of AP by AT (T-Line 400, Tensys Medical®, USA) and the direct intra-artery data in patients with cardiac comorbidities revealed the percentage error 56.8% for MAP, 42.7% for SAP, and 75.2% for DAP. 58 AT is used for central AP estimations based on the transfer functions radial artery-aorta. 59,60 AT of the radial artery may not be used in patients of the cardiac intensive care unit.…”
Section: Applanation Tonometrymentioning
confidence: 99%
“…In the literature, there are some artificial machine learning models for the estimation of oscillometric blood pressure. Tonometric measurement: Some pressure is applied on the wrist or arm [34][35][36][37][38][39][40][41][42]. Blood is not entirely stopped as it is in oscillometric and Korotkov's measurement systems.…”
Section: Noninvasive Blood Pressure Measurementmentioning
confidence: 99%
“…In the October issue, Greiwe et al [10] evaluated the performance of automated radial artery applanation tonometry using the T-Line 400 (Tensys Medical, San Diego, CA, USA) in awake or anesthetized patients in a cardiological ICU. The authors conducted a total of 27,900 measurements in 31 patients with severe cardiac comorbidities, including highly impaired left ventricular function, atrial fibrillation, and severe aortic valve stenosis (< 1.0 cm 2 ).…”
Section: Blood Pressure Monitoringmentioning
confidence: 99%